2013
DOI: 10.1007/s00027-013-0325-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a wastewater treatment plant on mercury contamination and sediment characteristics in Vidy Bay (Lake Geneva, Switzerland)

Abstract: Previous direct observations of the sediment surface in Vidy Bay, Lake Geneva (Switzerland), revealed a range of sediment characteristics in terms of colour, texture and morphology. Dives with the MIR submersibles during the éLEMO project permitted the exploration of a large portion of Vidy Bay. It is the most contaminated part of Lake Geneva, due to inputs of treated and untreated waters from a large wastewater treatment plant (WWTP). To evaluate the influence of WWTP effluent on mercury contamination and sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
4
8
0
Order By: Relevance
“…The proportion of MMHg to Hg tot was the highest at 1–2 cm (0.9–1.1 %) and decreased with depth to values between 0.28 % and 0.38 %. These Hg tot values and MMHg percentages are in line with analyses performed previously, but fall within the lower range of Hg concentrations reported for Vidy Bay [ 49 , 50 ]. Pearson's correlation analysis revealed that MMHg concentrations were positively correlated to C org , S tot , Fe II and Hg tot (Figure S3 ).…”
Section: Resultssupporting
confidence: 91%
“…The proportion of MMHg to Hg tot was the highest at 1–2 cm (0.9–1.1 %) and decreased with depth to values between 0.28 % and 0.38 %. These Hg tot values and MMHg percentages are in line with analyses performed previously, but fall within the lower range of Hg concentrations reported for Vidy Bay [ 49 , 50 ]. Pearson's correlation analysis revealed that MMHg concentrations were positively correlated to C org , S tot , Fe II and Hg tot (Figure S3 ).…”
Section: Resultssupporting
confidence: 91%
“…The magnitude of these effects depends on the types and the concentrations of contaminants in the sediments. All contaminant concentrations measured in the present study are in agreement with previous findings ( Haller et al, 2011 ; Gascon Diez et al, 2014 ; Masson and Tercier-Waeber, 2014 ; Gascón Díez et al, 2017 ; Loizeau et al, 2017 ). In addition, our results also revealed high concentrations of PAH (>13.5 μg kg –1 dw) in sediments collected at site 36.…”
Section: Discussionsupporting
confidence: 94%
“…Sediments in the Vidy Bay near the city of Lausanne were the most contaminated by metals, organic pollutants and organic matter ( Loizeau et al, 2017 ). The high contamination of sediments in this area has been documented for decades ( Grandjean et al, 1990 ; Poté et al, 2008 ; Loizeau et al, 2013 ; Gascon Diez et al, 2014 ; Masson and Tercier-Waeber, 2014 ). This is mainly due to historic inputs from urban sewage effluents ( Gascón Díez et al, 2017 ), which is also reflected by the prevalence of fecal-indicator bacteria ( Poté et al, 2008 ) and antibiotic-resistance genes ( Czekalski et al, 2014 ).…”
Section: Introductionmentioning
confidence: 89%
“…This site has been previously described by Graham, and detailed maps are presented in the Supporting Information (Figure S1). Briefly, NG2 is located at 138 m depth and 1100 m from an outlet pipe discharging in Vidy Bay both treated and untreated sewage water of a wastewater treatment plant (WWTP) located near the city of Lausanne. , …”
Section: Methodsmentioning
confidence: 99%